CONTENT TRANSFORMATION OF THE CONCEPT OF COMPETITIVENESS IN THE CONTEXT OF DIGITALIZATION OF HIGHER EDUCATION INSTITUTIONS - Bobro, Natalia (Social Economics, 2025)
The article is devoted to the content transformation of the concept of competitiveness of higher education institutions in the context of digitalization and the search for conceptual foundations for its systematization. In contemporary scientific literature, the competitiveness of universities is defined as a multidimensional and integrative category that combines the ability for sustainable development, long-term performance, and meeting the expectations of key stakeholders. At the same time, a significant number of studies interpret this concept in an overly simplified manner, reducing it either to a resource-based approach or to the university’s position in international rankings. Such an interpretation does not consider the complexity of modern challenges and does not allow competitiveness to be used as an effective tool for strategic management. It is substantiated that the digitization of higher education changes the logic of forming competitive advantages of universities and necessitates rethinking existing approaches. The research proposes to distinguish between universal-essential approaches that determine the general characteristics of competitiveness and descriptive-sectoral approaches that specify the content of this concept in the educational and scientific environment. The multi-level nature of competitiveness is highlighted: national (the country’s higher education system), regional (the educational space of individual territories), institutional (a specific university), and programmatic (educational programs). It has been proven that considering competitiveness in the context of a digital university requires the integration of strategic vision, resource potential, competence capabilities, and social mission. Particular attention is paid to the role of stakeholders and their interests, which shape the environment of cooperative interaction. Harmonizing the needs of internal and external partners is a basic condition for achieving long-term sustainability and competitive advantages for the university. The key areas in which the competitiveness of a digital university manifests itself have been identified: access to resources, the creation of competitive educational products and services, the ability of graduates to compete in the labor market, the development of innovative solutions, and ensuring the social function of higher education. The results of the research systematize modern approaches to understanding competitiveness and offer a conceptual framework for creating integrated models for its assessment. Such models should take into account the specifics of the digital educational environment, the dynamics of the educational and scientific services markets, the impact of digital technologies on the organization of the educational process, and the prospects for sustainable development. The practical significance of the results obtained lies in the possibility of using the established provisions to develop strategies for the development of universities seeking to strengthen their competitive positions in the global educational space. Further research should focus on testing integrated models in the real-world conditions of digital universities, which will allow for an assessment of their effectiveness and adaptability to a changing environment.